Exploitation of drainage water heat: A novel solution experimented at the Brenner Base Tunnel. (July 2023) - Tinti, F.; Spaggiari, C.; Lanconelli, M.; Voza, A.; Boldini, D.
Highlights: This paper illustrates a new system to exploit drainage water heat from tunnels. The heat exchange rate between the prototype and the drainage water is quantified. The conducted tests over the prototype verified the effective exploitable heat. The approach was implemented during the construction of the Brenner Base Tunnel. A generalization of the design method to other underground situations is proposed. Abstract: Deep tunnels in permeable fractured rock-masses and under high piezometric levels can drain notable volumes of warm water, which are collected under gravity in specific conduits towards the portals, where heat can be exploited. The utilization of this energy source is generally narrowed by the limited presence of end-users near the portals, while other promising heating and cooling needs can be found directly along the tunnel length. The work presents the design, construction and installation of a geothermal system prototype exploiting the drainage water heat directly inside the tunnel. The prototype was named Smart Flowing due to the peculiarity of its heat exchange process. The system was realized and installed inside the exploratory tunnel of the Brenner Base Tunnel, near the border between Italy and Austria. The Smart Flowing modules were built outside and later moved inside the tunnel, where they were placed and assembled concurrently to the advancement of the Tunnel Boring Machine. A design procedure was proposed and validated against a testing and monitoring campaign. The data from the experimental activity confirmed that the drainage water flow guarantees long-term stabilization of circulating water temperature and fast heat recovery afterwards, thus securing the considerable power and performance values of a water-water heat pump connected to the system. A sensitivity analysis allowed the reproduction of different working scenarios, in order to generalize the application of Smart Flowing beyond the specific installation context.